Improving Innovative Work Behavior in Small and Medium Enterprises: Integrating Transformational Leadership, Knowledge Sharing, and Psychological Empowerment - I Nengah Aristana; Ni Made Dwi Puspitawati; Putu Pradiva Putra Salain; Viktor Koval; Oksana Konarivska; Tetiana Paniuk (Societies)
Small and medium enterprises (SMEs) significantly contribute to society’s growth and welfare. Nevertheless, SMEs often experience challenges, i.e., high levels of competition and market demands. To maintain SMEs’ existence, a competitive advantage is demanded by increasing innovative work behavior. This study explores and evaluates the relationship between transformational leadership and innovative work behavior and examines the mediating role of knowledge sharing and psychological empowerment on the relationship between transformational leadership and innovative work behavior. This study uses a quantitative approach, where data were gathered from a questionnaire distributed to 190 employees of export SMEs and were further examined using Smart PLS 3.2.9. The findings demonstrate that transformational leadership does not influence innovative work behavior but significantly and positively influences psychological empowerment and knowledge sharing. Psychological empowerment and knowledge sharing significantly and positively influence innovative work behavior. Subsequently, psychological empowerment and knowledge sharing partially mediate the linkage between transformational leadership and innovative work behavior.